The genome sequence of the Dark Umber moth, Philereme transversata (Hufnagel, 1767) [version 1; peer review: 1 approved, 2 approved with reservations] - Douglas Boyes; Clare Boyes (Wellcome Open Research, 2025)
We present a genome assembly from a male specimen of Philereme transversata (Dark Umber; Arthropoda; Insecta; Lepidoptera; Geometridae). The genome sequence has a total length of 591.75 megabases. Most of the assembly (99.1%) is scaffolded into 20 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled, with a length of 16.07 kilobases. Gene annotation of this assembly on Ensembl identified 12,207 protein-coding genes.